Data for: When the music stops: Crossmodal effects of sounds on taste do not explain changes in liking - Swahn, Johan; Nilsen, Asgeir; Baptista, Iuri (Örebro University, 2026)
This dataset contains the data from a consumer sensory test with 515 participants evaluating six combinations of two chocolate ganache and three music conditions. Each participant tasted all six samples (2 ganache x 3 music conditions) in balanced monadic presentation and evaluated liking, sweetness, bitterness, and sourness. The data was collected in May 2018 at a food festival in Stockholm, Sweden.

Denna datauppsättning innehåller data från ett sensoriskt konsumenttest med 515 deltagare som utvärderade sex kombinationer av två chokladganacher och tre musiktillstånd. Varje deltagare smakade alla sex prover (2 ganacher x 3 musiktillstånd) balanserad monadisk presentation och utvärderade smak, sötma, bitterhet och surhet. Data samlades in i maj 2018 på en matfestival i Stockholm.
Data för: When the music stops: Crossmodal effects of sounds on taste do not explain changes in liking
Keywords: sensory evaluation; sensorisk bedömning; consumer research; konsumentundersökning; chocolate; choklad; ambience; atmosfär (anda); sense of taste; smaksinnet; multisensory experience; multisensorisk upplevelse; music; musik; Other Social Sciences; Annan samhällsvetenskap; OTHER; ÖVRIGT